MENINGKATKAN RASA PERCAYA DIRI DAN HASIL BELAJAR SISWA MELALUI MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING MATA PELAJARAN BAHASA INGGRIS PADA KELAS VIII-3 SMP NEGERI 7 MEDAN TAHUN AJARAN 2016/2017 - Roslina Lubis (Universitas Islam Negeri (UIN) Sumatera Utara, 2020)
This study aims to determine the improvement of student learning outcomes by using the CTL learning model on speaking competency standards. This type of research is PTK. The subjects of the research were students of class VIII-3 SMP Negeri 7 Medan. Based on the results of this study, it shows that in the learning outcome test in cycle I, the number of student learning completeness reached 28 students (93.33%) with an average of 78. In cycle II the total student learning completeness reached 26 students (86.67%) with an average of 78 students. an average of 73.83 is said to have not increased then it will be continued to the third cycle. In the learning outcomes test in cycle III, the number of student learning completeness reached 29 students (96.67%) with an average of 79.50